Caracterização física, química e mineralógica dos solos de encostas sob diferentes sistemas de uso. - Sousa, Cristiano dos Santos (2015)
Soil is the natural resources the most exploited in the world, mainly due to the current need for food production. However, the use of agricultural practices mistakenly brings the degradation of their properties, especially in rugged areas. Thus the research aimed to evaluate the chemical, physical and mineralogical soil at different positions in the landscape, in soils under the use of Agriculture, Pasture and Forest-native, in Areia-PB, micro-region of Brejo Paraibano. Samples were collected in eighteen (18) points in the areas of agriculture and grazing, and six (6) points in kills native area in three relief positions (Top, middle and bottom) and at three depths (0 -10, 10-20 and 20-40 cm) between January and June 2014. The samples were subjected to soil texture analysis, physical and chemical attributes, and analysis of fluorescence X-ray and diffraction X-ray for the characterization of total oxides and mineralogy. The tests were performed at the Physics Laboratory of Department of Soil Soil and Rural Engineering - DSER / UFPB / Campus II, in the Laboratory of Analytical Chemistry of the National Institute for the Semi-Arid – INSA, in the New Materials Technology Laboratory (LTNM) of Development Institute of the State of Paraíba – UFPB and Rapid Solidification Laboratory of Technology Center of the Federal University of Paraíba (Campus I). In the mineralogical composition of the agricultural area of the samples was evidenced the predominance of primary minerals such as quartz, supporting the textural classification of the soil of the area. In the forest area, the mineralogical composition was homogeneous, with the predominance of quartz and kaolinite and goethite occur in all collected points, while the pasture area is composed mainly of quartz, kaolinite and feldspar. In the physical analysis were observed Sandy and clayey-sandy textures in the areas of use of Agriculture, Forest and Pasture, respectively. According to the results of chemical properties, the area of Agriculture presented a greater supply of nutrients, especially the P content in the soil in the Top Third position (101.50 mg dm-3), showing the effect of transport material on the side and not as differing depths (91,53a, 87,38a and 76,23a mg dm-3, respectively). The forest area showed most of the nutrients concentrated in the depth of 0-10 cm and higher acidity among the evaluated areas, but almost no effect on the positions on the slope. The grassland area had higher Ca2+ levels (1,03a cmolc dm-3) and K + (0,23a cmolc dm-3) in the Bottom third position and a greater concentration of P in the Top Third position (43,10a mg dm-3). In the analysis of total oxide content it was observed that P2O5 content of the agricultural area was higher at shallow depths, as well as in the bottom third position (0.45, 0.42 and 0.36%, in their depths). In the forest area there was higher Al2O3 contents when compared with other areas, while the pasture area presented oxide contents near the Agricultural Area results.